A study on the minimum inhibitory concentration and minimum bactericidal concentration of Nano Colloidal Silver on food-borne pathogen - Petrus, E. M.; Santhrakumaru, Tinakumari; Chai, Lay Ching; Anyi, Ubong; Robin, Tunung; Nillian, Elexson; Chai, Li Fen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
In the emerging issue of increased multi-resistant properties in foodborne pathogens, silver nano particles are being used increasingly as antimicrobial agents. Thus, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Nano Colloidal Silver towards food-borne pathogens such as Escherichia coli O157:H7, Listeria monocytogenes, Salmonella enterica Serovar Typhi, Vibrio cholerae, Vibrio parahaemolyticus, Bacillus cereus and Staphylococcus aureus were examined in this study. The results obtained suggested that Nano Colloidal Silver exhibit a good bacteriostatic effect but poor bactericidal effect towards all food-borne pathogens tested. Nano Colloidal Silver can be a potential antimicrobial agent due to its low cost of production and high effectiveness in antimicrobial properties, which may find wide applications in various food industries to address food safety issues.